Air distribution by interaction of counter non coaxial air jets at pulsing mode - Voznyak, Orest (Видавництво Львівської політехніки, 2013)
Air distribution by interaction of counter non coaxial air jets at pulsing mode has been considered. Dynamic parameters of air flow that is created due to interaction of counter non coaxial flat air jets at their leakage at pulsing mode and creation of dynamic indoor climate in a room has been determined. Розглянуто повітророзподіл при взаємодії зустрічних неспіввісних струмин в пульсуючому режимі. Визначено параметри результуючого повітряного потоку для створення динамічного мікроклімату у приміщенні.
Keywords: air distribution; flat air jet; pulsing mode; dynamic indoor climate; jets interaction; counter non coaxial jets; air velocity; flow rate; повітророзподіл; плоскі повітряні струмини; пульсуючий режим; динамічний мікроклімат; не співвісні струмини; швидкість повітря; витрата повітря